Journey of Niger from undulated lands - Bisen, Rajani; Tiwari, V N; Sujatha, M (Indian Farming, 2022)
Due to the wide adaptability of the variety JNS-28, now this crop is being grown in plains also. This crop can replace soybean crop in plains up to certain extent as soybean crop is no more economical to the farmers of this belt. The farmers fetched 9.25 q/ ha seed yield in niger crop which is almost double the productivity of the Madhya Pradesh state and additional income of `15385/ha over the soybean crop. The shifting of the crop from the hilly areas to plain land is a very big achievement as the farmers earlier were not very confident about the crop. But as the farmers observed that niger has the withstanding capacity of heavy rains and stagnant water up to 2–3 days it can be taken up as a replacement to soybean crop. The same initiative can be replicated as cluster demonstration in other niger growing states, viz. Odisha, Chhattisgarh, Andhra Pradesh, Bihar, Jharkhand and Karnataka